Entrusting the Future of Rural Society through Nurturing Civic Pride: Endeavors in Gojome Town, Akita Prefecture of Japan - Kusakari, Yasuko; Chiu, Dominique; Muasa, Lillian; Takahashi, Kyoko; Kudo, Shogo (Consilience, 2018)
This photo essay illustrates a study on endeavors in a rural Japanese town with a declining population and discusses the future of rural society from a perspective of civic pride as well as sustainability. The population of the town of Gojome, located in Akita Prefecture of northern Japan, has halved from 20,025 in 1960 to 9,481 in 2015. Depopulation is often perceived as a half-empty glass, but we approached our study with the view that it is half-full. We discuss the issue through appreciative approaches by adopting the concept of “civic pride” as an alternative lens based on our empirical survey. The methodology adopted for this field survey include individual interviews with 126 respondents (consisting of 79 residents of Gojome and 47 individuals who were visiting the town) across different generations, 15 key informant interviews, drawings of their pride about the town by 34 sixth-graders of Gojome Elementary School, and observations. It was found that various generations of proud Gojome locals and non-locals have started to proactively participate in the process of bettering the town through various social, cultural, economic, and environmental activities. Based on our learning in Gojome town we conclude that, in the wake of rural depopulation, nurturing “civic pride” could potentially contribute to rural sustainability through entrusting the future of rural society to next generations.